P89 Ambulatory oxygen assessments in COPD and pulmonary fibrosis. (2nd December 2011) - Heslop, K; Stenton, C; Irving, C
Abstract : Background: Between 2006 and 2011, 161 patients were referred for formal ambulatory oxygen assessment at the Newcastle RVI. Their results have been reviewed. Method: The assessments comprised three 6-min walk tests (6MWT) supervised by a trained healthcare professional as per BTS guidelines (2006). Test 1: On room air (RA) Test 2: On room air with the oxygen supply switched off Test 3: On oxygen 4 l/min via nasal cannulae Minimum SpO2 during exercise, distance walked and oxygen flow rate required to maintain SpO2 above 90% were recorded together with the respiratory diagnosis and basic demographic details. Results: 18 patients were excluded as they did not de saturate on walk 1 or were unable to complete the 6MWT. 143 patients' results were analysed. 82 were male with 61 female. The two commonest clinical diagnoses were Interstitial Pulmonary Fibrosis (IPF) and COPD. IPF patients walked on average 70 m (31%) further than COPD patients on room air. They had the greatest increase in oxygen saturation when exercising on supplemental oxygen (12%) but had the lowest improvement in walking distance (7.3%). There was no relationship between improvement in walk test distance and improvement in oxygenation in any of the subgroups. Conclusion: Further studies may be needed to explore the relative benefits of ambulatory oxygen in non-COPD patients.